Genetic improvement of mungbean and urdbean and their role in enhancing pulse production in India - Singh, D. P.; Singh, B. B.; Pratap, Aditya (The Indian Journal of Genetics and Plant Breeding, 2017)
The initial varietal development in mungbean and urdbean focused mainly on selection from landraces or the germplasm samples collected, purified and evaluated. However, systematic efforts were made by National Agricultural Research System comprising Indian Council of Agricultural Research and State Agricultural Universitiesthrough All India Coordinated Pulses Improvement Projectfor varietal improvement. National Bureau of Plant GeneticResources and AICPIP centres collected over 8,000 Vignagenetic resources and also introduced germplasm fromother countries and made them available for evaluation.Several resistant donors were identified and used to transfergene(s) for biotic stresses. As a result, a number of highyielding varieties were developed through intraspecifichybridization. Large numbers of these varieties are resistantto one or more major diseases of the specific agro-eclogicalniches. Six varieties in mungbean and two in urdbean werealso developed through inter-specific hybridization whichhad new plant type and resistance to prevalent diseases.However, limited success has been achieved for thedevelopment of varieties with resistance to insect-pestsand abiotic stresses. There is a need to intensify researchin these areas through introgression of desirable allelesfrom secondary and tertiary gene pool into the cultivatedtype for yield, photo period and temperature insensivityand insect pest tolerance. The onset of genomics providesmassive amount of information, but the success will dependon precise phenotyping to achieve desired restructuring inexisting plant type.